1993
DOI: 10.1038/361263a0
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channel stimulation by natriuretic peptides through cGMP-dependent dephosphorylation

Abstract: Natriuretic peptides inhibit the release and action of many hormones through cyclic guanosine monophosphate (cGMP), but the mechanism of cGMP action is unclear. In frog ventricular muscle and guinea-pig hippocampal neurons, cGMP inhibits voltage-activated Ca2+ currents by stimulating phosphodiesterase activity and reducing intracellular cyclic AMP; however, this mechanism is not involved in the action of cGMP on other channels or on Ca2+ channels in other cells. Natriuretic peptide receptors in the rat pituita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
132
3

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(144 citation statements)
references
References 28 publications
9
132
3
Order By: Relevance
“…Furthermore, erythrocytes have guanylate-cyclase activity stimulated by these ANP fragments like other cells with well-established ANP-specific receptors (Brenner et al, 1990;Leitman et al, 1986Leitman et al, ,1988O'Donnell et al, 1986O'Donnell et al, ,1987Owen et al, 1987;Smith and Lincoln, 1987;White et al, 1993). We suggest therefore that human erythrocytes can be target cells for ANP fragments possessing at least Phe-Arg and Ser-Ser at the carboxy and amino termini, respectively, in the blood stream.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, erythrocytes have guanylate-cyclase activity stimulated by these ANP fragments like other cells with well-established ANP-specific receptors (Brenner et al, 1990;Leitman et al, 1986Leitman et al, ,1988O'Donnell et al, 1986O'Donnell et al, ,1987Owen et al, 1987;Smith and Lincoln, 1987;White et al, 1993). We suggest therefore that human erythrocytes can be target cells for ANP fragments possessing at least Phe-Arg and Ser-Ser at the carboxy and amino termini, respectively, in the blood stream.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of Ser-Ser at the amino terminus also reduced the potencies of ANP peptides to stimulate vasorelax-ation Owen et al, 1987) and to act on cellular Na+/K+ cotransport O'Grady et al, 1985;Owen et al, 1987). cGMP mediates some of the physiological effects of ANP (Brenner et al, 1990) including alterations of ion-transport systems (Clemo et al, 1992;O'Donnell et al, 1986;White et al, 1993). We have shown that, like other cell types (Leitman et al, 1988;Smith and Lincoln, 1987), the addition of ANP-I11 (10 pM) to erythrocytes produces a rapid but transient increase in cellular cGMP concentration (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism suggests that PKG activates maxi-K channels through a direct phosphorylation of the channel protein or a regulatory subunit (17, 19 -21); this process can be reversed by phosphatase 2A (22). In contrast, the second mechanism proposes that PKG activates maxi-K channels indirectly via a PKG-dependent activation of protein phosphatase 2A (23,24), which may directly dephosphorylate maxi-K channels. Alternatively, protein phosphatase 2A may exert its effect indirectly.…”
mentioning
confidence: 98%
“…This may be another general mechanism contributing to the reduction in [Ca2~]~produced by cGMP agonists in many cells. cGMP and PKG stimulate Ca2-activated potassium channels in rat pituitary tumor cells (White et al, 1993). These effects are mimicked by ANP, are preceded by a rapid and potent stimulation of cGMP production, and require PKG activity.…”
Section: Ion Channelsmentioning
confidence: 99%
“…The phosphatase inhibitor okadaic acid blocks the effect of PKG, revealing a requirement for protein dephosphorylation. The PKG substrate mediating this action has been suggested to be phosphatase 2A itself or a regulator of this enzyme (White et al, 1993), a proposal yet to be directly tested. Regulation of Ca2~-activatedKc hannels by PKG has also been shown in neurons.…”
Section: Ion Channelsmentioning
confidence: 99%